Photoinduced Charge-Carrier Generation in Epitaxial MOF Thin Films: High Efficiency as a Result of an Indirect Electronic Band Gap? - Liu, Jinxuan; Zhou, Wencai; Liu, Jianxi; Howard, Ian; Kilibarda, Goran; Schlabach, Sabine; Coupry, Damien; Addicoat, Matthew; Yoneda, Satoru; Tsutsui, Yusuke; Sakurai, Tsuneaki; Seki, Shu; et al. (Angewandte Chemie International Edition, 2015)
For inorganic semiconductors crystalline order leads to a band structure which gives rise to drastic differences to the disordered material. An example is the presence of an indirect band gap. For organic semiconductors such effects are typically not considered, since the bands are normally flat, and the band-gap therefore is direct. Herein we show results from electronic structure calculations demonstrating that ordered arrays of porphyrins reveal a small dispersion of occupied and unoccupied bands leading to the formation of a small indirect band gap. We demonstrate herein that such ordered structures can be fabricated by liquid-phase epitaxy and that the corresponding crystalline organic semiconductors exhibit superior photophysical properties, including large charge-carrier mobility and an unusually large charge-carrier generation efficiency. We have fabricated a prototype organic photovoltaic device based on this novel material exhibiting a remarkable efficiency.
CRIS-Team Scopus Importer:2023-03-20
Keywords: metal-organic frameworks; photocarrier mobility; photovoltaic device; porphyrin; semiconductors